Performance of Sweet Pepper under Protective Structure in Gazipur of Bangladesh - Halim, GMA; Islam, MS (International Journal of Environment, 2013)
Evaluation of sweet pepper cultivation under different protective structures was made in two consecutive seasons of 2007-08 and 2008-09 at the experimental field of Horticulture Research Center of BARI, Gazipur. One popular commercial capsicum variety California Wonder was included in the study with four protective structures (low height poly tunnel, polytunnel with side open, poly tunnel with side closed and poly house) including control (open field). Protective structures had remarkable and significant influence on plant growth and yield of sweet pepper. The plants grown under protective structures had higher plant height compared to that of plants grown in open field. The highest individual fruit weight (65.2g) was recorded form the plants grown under poly house condition while it was the lowest from open field grown plant (3.34 g). More than five fruits were harvested when the plants were grown under poly tunnel (side closed) or poly house. The maximum fruit yield per plant (334.0g) was recorded from poly house, which was 160.4% higher than that of plants grown under open field condition. The second highest yield was recorded from the plants of poly tunnel (212.5) indicating bright scope for sweet pepper cultivation under protective structures. DOI: http://dx.doi.org/10.3126/ije.v1i1.8523 International Journal of Environment Vol.1(1) 2013: 1-8